Strong coupling Hartree-Fock approximation in the dynamical mean-field theory - Shvaika, A.M. (Condensed Matter Physics, 2001)
In the limit of infinite spatial dimensions, a thermodynamically consistent
theory, which is valid for arbitrary value of the Coulombic interaction ( U <
∞ ), is built for the Hubbard model when the total auxiliary single-site problem
exactly splits into four subspaces with different “vacuum states”. Some
analytical results are given for the Hartree-Fock approximation when the 4-
pole structure for Green’s function is obtained: two poles describe contribution
from the Fermi liquid component, which is ferromagnetic and dominant
for small electron and hole concentrations (“overdoped case” of high- Tc ’s),
whereas other two describe contribution from the non-Fermi liquid, which
is antiferromagnetic and dominant close to half filling (“underdoped case”). Для моделі Хаббарда побудовано термодинамічно самоузгоджену
теорію, яка застосовна для довільних значень кулонівської кореляції
( U < ∞ ) в границі безмежної розмірності простору, коли повна допоміжна задача точно розпадається на чотири підпростори з різними “вакуумними станами”. Наведено ряд аналітичних результатів для
наближення Хартрі-Фока, коли отримується чотириполюсна структура для функцій Гріна: два полюси описують внески Фермі-рідинної
компоненти, яка є феромагнітною і домінує при малих концентраціях електронів або дірок (“перелегований випадок” ВТНП), а інші два
– внески від не-Фермі рідини, яка є антиферомагнітною і домінує поблизу половинного заповнення (“недолегований випадок”).